Measurement of vibrational and rotational temperature in spark-discharge plasma by optical emission spectroscopy: Change in thermal equilibrium characteristics of plasma under air flow. (September 2019) - Kinoshita, Masao; Fuyuto, Takayuki; Akatsuka, Hiroshi
The vibrational and rotational temperatures in a spark-discharge plasma were measured using optical emission spectroscopy, and the influence of the air flow velocity and ambient pressure on these temperatures was investigated. The optical emissions from the plasma were led to an imaging spectroscope through an optical fiber. The temperature was estimated by fitting a theoretically calculated spectrum to that which had been acquired experimentally, formed by nitrogen molecule emission from 372 to 382 nm. The spark-discharge plasma was examined with a flow of ambient air at a discharge energy of 80 mJ. The air flow caused the spark-discharge channel to elongate downstream. At the center of the spark plug gap, the vibrational temperature in the plasma was 4000 K, whereas the rotational temperature was 2000 K. This plasma can be regarded as being in non-thermal equilibrium because the vibrational temperature was higher than the rotational temperature. At a position approximately 3 mm downstream from the spark plug gap, the vibrational and rotational temperatures increased to 4500 and 4000 K, respectively, while approaching each other. Both temperatures reached a maximum value. These results show that the plasma transitions from non-thermal equilibrium to thermal equilibrium as it is elongated by the air flow. Ignition efficiency improvements can be expected if the time required to transition from non-thermal to thermal equilibrium can be shortened.